2008
DOI: 10.1104/pp.107.110841
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Germination Transcriptional Program Using Small Molecules    

Abstract: The transition from seed to seedling is mediated by germination, a complex process that starts with imbibition and completes with radicle emergence. To gain insight into the transcriptional program mediating germination, previous studies have compared the transcript profiles of dry, dormant, and germinating after-ripened Arabidopsis (Arabidopsis thaliana) seeds. While informative, these approaches did not distinguish the transcriptional responses due to imbibition, shifts in metabolism, or breaking of dormancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 52 publications
5
94
0
Order By: Relevance
“…each of these proteins are not expressed at high levels in nongerminating Arabidopsis seeds (28,29) (Fig. 2G and SI Appendix, Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…each of these proteins are not expressed at high levels in nongerminating Arabidopsis seeds (28,29) (Fig. 2G and SI Appendix, Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Given that low seed maturation temperature leads to high dormancy at warm imbibition temperatures ( Figure 1A), and at warmer temperatures FLC was shown to have little or no role (Chiang et al, 2009), we investigated whether CBF-dependent pathways have a role in dormancy induction by low maturation temperatures. Investigation of available microarray data using the EFP browser (Bassel et al, 2008) also suggested that CBFs might be expressed during seed development. To analyze the temperature regulation of CBF transcription in seeds, we performed time-course experiments in which seeds or seedlings were transferred from 22 to 48C and the expression of CBF1 recorded by RT-PCR.…”
Section: Genetic Regulation Of Strong Dormancy Induced By Cool Seed Mmentioning
confidence: 99%
“…For this in silico analysis, we used the seed-specific eFP browser and the eNorthern tool (available at www.bar.utoronto.ca) to access diverse transcriptome data sets not only of Arabidopsis seed germination but also of seed development as a distinct developmental process (Toufighi et al, 2005;Winter et al, 2007;Bassel et al, 2008). Altogether, 101 different microarray experiments focusing on diverse treatments, mutants, tissues, and developmental processes of Arabidopsis seeds were analyzed (see Supplemental Data Set 2 online).…”
Section: Comparison Of Brassicaceae Seed Development and Germination mentioning
confidence: 99%